Analisis Pengaruh Tata Kelola Perusahaan Terhadap Efisiensi Investasi Pada Perusahaan Sektor Perbankan Terdaftar BEI - Azzahra, Salsabila; Ramadhan, Yanuar (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of corporate governance on investment efficiency in banking sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. Corporate governance in this study is proxied through five variables adapted from the 2017 ASEAN Corporate Governance Scorecard (ACGS): shareholder rights, fair treatment of shareholders, stakeholder roles, disclosure and transparency, and board responsibilities. This study uses a quantitative approach with secondary data obtained from company annual reports. Data were analyzed using multiple regression analysis techniques with the help of SPSS. The results show that stakeholder roles have a significant effect on investment efficiency, while other variables have no statistically significant effect on investment efficiency. These findings suggest that strong stakeholder involvement, including regulatory oversight, can improve capital allocation efficiency by reducing over-investment practices.